The synthesis of CuxS from Cu layers by low pressure plasma processing - Ball, J.; Lane, David W.; Reehal, H. S. (Elsevier, 2017)
A new method of converting Cu layers to CuxS on glass at low pressure using an electron cyclotron resonance plasma and SF6 gas is presented. The process operates at low temperatures and short time scales. Trends in film crystallinity and morphology are identified in relation to process time and temperature. These show that sulphurisation is most likely complete within 10 min and that the sulphur content of the films reduces as the conversion temperature is increased from 473 to 623 K. Optical measurements show that the films have a direct bandgap of ∼2.5 eV which is consistent with published values for CuxS films grown by other techniques. Analysis by SEM has revealed that the films possess a complicated structure of platelets covering a denser underlying film. This may account for the differences in observations made by XRF and Raman spectroscopy, which both indicated a mixture of CuS and Cu2S, and X-ray diffraction which predominantly showed CuS.
Keywords: Semiconductors; Thin films; Vapour deposition; SEM; X-ray diffraction